Jesus in the Gospels : a biblical christology - Schnackenburg, Rudolf, 1914-2002. (1995)
"According to Rudolf Schnackenburg, a truly historical portrait of Jesus is unattainable because the primary sources written about Jesus were not historical records as such. What is attainable, however, is a faith interpretation of Jesus' life and works, gleaned from the writings of those closest to the life of Christ : the four Gospels. Schnackenburg here provides a full faith interpretation of Jesus as each Gospel community portrayed him. Numerous commonalities about Jesus among these Gospels are revealed, and a fully recognizable portrait of Jesus emerges."--Page 4 of cover.
4. Luke -- I. The basic view -- The one sent by GOd in the power of the Holy Spirit -- The proclaimer of the gospel of grace -- The Savior, Messiah, and Lord presented to the Jews and Greeks -- The exalted Lord who went to God through death and resurrection -- The guide to salvation -- The Lord who is coming again -- II. Individual features -- Jesus' humanity -- Jesus' efforts for the poor and suffering -- Jesus' devotion to women -- Jesus at prayer -- 5. John -- I. Approaching the Gospel of John and its Christology -- The historical dimension -- The Gospel of John as a gospel writing -- The structure of the Gospel of John -- The Johannine picture of Christ in comparison with the Synoptic Gospels -- A hermeneutical approach to the Johannine picture of Christ -- II. Individual assertions of Johannine Christology -- The one who is sent -- The Son who is close to His Father -- The Son of Man who came down from heaven and ascends there again -- The eschatological prophet -- The Lamb of God -- The preexistent and incarnate Logos -- 6. The gospel in four forms as manifold and yet unified testimony to Christ -- I.A varied picture of Jesus Christ -- The picture in the gospels -- Matthew's modification of the Markan picture of Jesus -- The Lukan picture of Jesus in comparison with Mark and Matthew -- The transition to Johannine Christology -- II. The unified faith-picture of Jesus Christ that underlies the various sketches -- The conviction that Jesus is the Messiah -- Faith in Jesus, the Son of God -- Jesus the bringer of salvation -- The wholly other, who witnesses among human beings to God and His majesty -- III. The evangelists' faith-picture of Jesus Christ in relation to the historical Jesus of Nazareth -- IV. Outlook.
Includes bibliographical references (pages 326-371) and index.
Translation of: Person Jesu Christi im Spiegel der vier Evangelien.
Keywords: Jesus Christ -- History of doctrines -- Early church, ca. 30-600.; Jesus Christ -- Person and offices -- Biblical teaching; Bible. -- Theology